Optimality Theory and Syntactic Constraints in English and Arabic Prepositional Phrases: A Comparative Analysis (The International Journal for Scientific Research, 2023)
This research paper aimed to investigate the syntactic constraints that govern the use of prepositional phrases in English and Arabic, using Optimality Theory (OT) framework. A set of English and Arabic sentences containing prepositional phrases were collected and analyzed for constraint violations. This study compared the syntactic structures of prepositional phrases in both languages by examining the case marking, headedness, and subject-verb agreement requirements of OT. The findings indicated that although prepositional phrases are used similarly in Arabic and English, there are also structural variations between them.  In particular, the study finds that Arabic prepositional phrases exhibit more markedness and complexity than English preposition phrases, due to the influence of case marking and agreement constraints in OT. The study contributes to our understanding of the syntactic structures of preposition phrases in both languages and highlights the importance of considering the role of syntactic constraints in language comparison studies.
Keywords: Optimality theory; preposition phrase; agreement; constraint ranking